Numerical analysis of methane hydrate decomposition experiments by depressurization around freezing point in porous media - Li, Bo; Liang, Yun-Pei; Li, Xiao-Sen; Wu, Hui-Jie (Fuel, 2015)
The depressurization-induced decomposition behaviors of methane hydrate around the freezing point in porous media are investigated in this numerical study. A total of three cases have been simulated in a cylindrical reactor using a central vertical well with the production pressure P-W = 2.20, 2.60, and 3.00 MPa, respectively. The simulation results of the pressure and temperature profiles and gas production processes are then compared with the corresponding experimental data. Both the experimental and numerical results indicate the existence of a "freezing stage'' in the case of P-W = 2.20 MPa (Case 1). Four phases of gas, liquid, ice, and hydrate are observed to coexist in the reactor in this freezing stage. Comparing with other two cases, the hydrate dissociation in Case 1 is promoted by three kinds of heat: the reservoir sensible heat Q(S), the conducted heat from the boundaries Q(B), and the latent heat from ice transition Q(I). It is found that the Q(S) and Q(I) play an important role in promoting the fastest hydrate dissociation in the early depressurization stage of Case 1. In addition, the ice phase is found to be formed in the central area of the hydrate deposit and in the vicinity of the production well. Although the formed ice may cause flow blockage for the gas and water, the released latent heat is still attractive for the fast hydrate dissociation under depressurization around the freezing point. (C) 2015 Elsevier Ltd. All rights reserved.